2022
DOI: 10.3390/cells11182793
|View full text |Cite
|
Sign up to set email alerts
|

Boosting the Immune Response—Combining Local and Immune Therapy for Prostate Cancer Treatment

Abstract: Due to its slow progression and susceptibility to radical forms of treatment, low-grade PC is associated with high overall survival (OS). With the clinical progression of PC, the therapy is becoming more complex. The immunosuppressive tumor microenvironment (TME) makes PC a difficult target for most immunotherapeutics. Its general immune resistance is established by e.g., immune evasion through Treg cells, synthesis of immunosuppressive mediators, and the defective expression of surface neoantigens. The succes… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 274 publications
(280 reference statements)
0
5
0
1
Order By: Relevance
“…[211] Studies also indicated that irreversible electroporation has immunomodulatory activity and increases the level of tumor-infiltrating cells, decreases the level of regulatory T (T reg ) cells, and improves the therapeutic effect of immune checkpoint blockade. [212][213][214][215][216]…”
Section: Eliminating Diseased or Cancerous Cellsmentioning
confidence: 99%
“…[211] Studies also indicated that irreversible electroporation has immunomodulatory activity and increases the level of tumor-infiltrating cells, decreases the level of regulatory T (T reg ) cells, and improves the therapeutic effect of immune checkpoint blockade. [212][213][214][215][216]…”
Section: Eliminating Diseased or Cancerous Cellsmentioning
confidence: 99%
“…Despite the growing number of trials combining RT and ICI, whether the RT regimen in combination with ICI is the appropriate choice remains an open question, especially considering factors such as the timing of the radiation [5], sequencing [6], and patient selection [7]. Numerous studies [8][9][10][11][12] have investigated the integration of these treatments based on preclinical evidence demonstrating a synergistic interaction between them. However, it remains unclear how to optimally integrate these therapeutic modalities in the treatment of cancer patients.…”
Section: Introductionmentioning
confidence: 99%
“…Although the first therapeutic cancer vaccine approved more than a decade ago targeted prostate tumors (sipuleucel-T), the clinical efficacy of immunotherapy for treating PCa remains limited, with poor responses to checkpoint inhibitors as monotherapy [3]. PCa tumors display an immunosuppressive tumor microenvironment mediated by reduced expression of human leucocyte antigen (HLA) surface expression, decreased neoantigen expression, phosphatase and tensin homolog (PTEN) protein loss, and dysfunction of interferon (IFN) type I signaling [4-5]. These factors contribute to low response rates to checkpoint inhibitors in most cases of mCRPC, except for MSI-H tumors and those with CDK12 mutations [6-7].…”
Section: Introductionmentioning
confidence: 99%